2021
DOI: 10.1093/jpepsy/jsab125
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Experiences of Childhood Cancer During the COVID-19 Pandemic: An Australian Perspective

Abstract: Introduction COVID-19 has had far-reaching impacts including changes in work, travel, social structures, education, and healthcare. Objective This study aimed to explore the experiences of parents of children receiving treatment for cancer during the COVID-19 pandemic. Methods Parents whose children were currently in treatment for childhood cancer or had comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
0
17
2
Order By: Relevance
“…COVID‐19 and associated visitor restrictions have greatly impeded centers’ abilities to meet the standard of family‐centered care 36 . Siblings now have even less access to hospital‐based services, due to strict infection control efforts 37,38 . Many of these new policies may be retained post‐pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID‐19 and associated visitor restrictions have greatly impeded centers’ abilities to meet the standard of family‐centered care 36 . Siblings now have even less access to hospital‐based services, due to strict infection control efforts 37,38 . Many of these new policies may be retained post‐pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…36 Siblings now have even less access to hospital-based services, due to strict infection control efforts. 37,38 Many of these new policies may be retained postpandemic. Thus, this study's findings likely substantially underestimate the gaps in current sibling care practices.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge of participant recruitment for health behavior interventions among children diagnosed with cancer is common [ 8 , 41 ]. However, our challenges may have been exacerbated because of recruitment from a single site and parents not wanting to commit to research interventions because of the unknown risk of COVID-19 for unvaccinated children diagnosed with cancer and their immunocompromised status [ 42 ]. Despite the lower-than-anticipated opt-in rate, the retention rate and program engagement were high, demonstrating that once the survivors expressed interest in the iBounce program, they were highly receptive to it.…”
Section: Discussionmentioning
confidence: 99%
“…A study in UK found that parents/caregivers were worried that their children would get infected by the virus and felt that hospital was not a safe place, thus increasing parents' anxiety and concerns about their child's care. 26,27 Another study also stated that hospital restriction increased parent's psychosocial distress during the pandemic, especially regarding the risk of suboptimal care received by their children. [27][28][29] There are limited data on the mental health status of pediatric patients with cancer during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%